ANALISA KINERJA TURBIN ANGIN SUMBU HORIZONTAL MENGGUNAKAN AIRFOIL NACA 6510 TIPE TAPERLESSTERHADAP VARIASI KECEPATAN ANGIN DAN JUMLAH SUDU DENGAN SIMULASI CFD - Alfa Nico Immanuel (2021)
Wind turbine is a device that is able to convert wind energy into mechanical energy and then converted into electrical energy through a generator. This turbine varies the number of blades, namely 2 and 3 blades and the wind speed varies from 11,13, and 15 m/s. This bar uses an international airfoil unit, namely NACA (National Advisory Committee for Aeronautics) which uses 4 digits, namely 6510. This analysis is carried out on CFD software whose parameters have been determined calculated through geometric calculations, and the blade design is carried out in CAD software from the data inputted by geometry calculations. The finished designs on 2 blades and 3 blades are then directly analyzed in CFD software which is carried out in several stages from modeller diagrams, mesh, set up, and results. Set up is an analysis to get the results of the blade design on 2 blades and 3 blades and get the results that the Cp value on 2 blades is 0.65, 0.72, and 0.8 and also 3 blades is 0.69, 0.8 , and 0.9 with TSR that has been obtained results are 5.6, and 7.